2016
DOI: 10.1096/fj.201600603r
|View full text |Cite
|
Sign up to set email alerts
|

Heme acquisition in the parasitic filarial nematode Brugia malayi

Abstract: Nematodes lack a heme biosynthetic pathway and must acquire heme from exogenous sources. Given the indispensable role of heme, this auxotrophy may be exploited to develop drugs that interfere with heme uptake in parasites. Although multiple heme-responsive genes (HRGs) have been characterized within the free-living nematode Caenorhabditis elegans, we have undertaken the first study of heme transport in Brugia malayi, a causative agent of lymphatic filariasis. Through functional assays in yeast, as well as heme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 59 publications
(83 reference statements)
1
26
0
1
Order By: Relevance
“…Since this first experiment, RNAi has been successfully applied to a number of mammalian-parasitic nematode species, including Ascaris suum, B. malayi, Onchocerca volvulus, the ruminant parasite Haemonchus contortus and the filarial parasite of livestock Setaria digitata (Hagen et al, 2012;Luck et al, 2016;Maule et al, 2011;McCoy et al, 2015;Misra et al, 2017;Samarasinghe et al, 2011;Somarathne et al, 2018;Verma et al, 2017). However, results from RNAi experiments are often variable in terms of both the extent of gene knockdown and the resulting mutant phenotype (Britton et al, 2016;Hagen et al, 2012;Maule et al, 2011;McCoy et al, 2015).…”
Section: Rnai In Parasitic Nematodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this first experiment, RNAi has been successfully applied to a number of mammalian-parasitic nematode species, including Ascaris suum, B. malayi, Onchocerca volvulus, the ruminant parasite Haemonchus contortus and the filarial parasite of livestock Setaria digitata (Hagen et al, 2012;Luck et al, 2016;Maule et al, 2011;McCoy et al, 2015;Misra et al, 2017;Samarasinghe et al, 2011;Somarathne et al, 2018;Verma et al, 2017). However, results from RNAi experiments are often variable in terms of both the extent of gene knockdown and the resulting mutant phenotype (Britton et al, 2016;Hagen et al, 2012;Maule et al, 2011;McCoy et al, 2015).…”
Section: Rnai In Parasitic Nematodesmentioning
confidence: 99%
“…Understanding the sensory mechanisms used by these parasites to find and infect hosts, and to recognize and respond appropriately to the host environment, may lead to the development of traps, repellents or drugs that block these processes (Bryant and Hallem, 2018b; Gang and Hallem, 2016). In addition, parasitic nematodes need to acquire essential metabolites, including heme and cholesterol, from their hosts (Chitwood, 1999;Luck et al, 2016). Identifying parasite-specific proteins used for nutrient uptake and metabolism could yield novel drug targets (Salinas and Risi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic evidence suggests that the gut is functional, as the intestine is rich in proteolytic enzymes and transporters that may be involved in absorption and digestion of nutrients ( Morris et al, 2015 ). A recent study has also shown that a heme transporter (BmHRG-1) is functional in B. malayi and localizes both to the endocytic compartments and cell membrane when expressed in yeast ( Luck et al, 2016 ), further supporting the concept that the gut plays a role in nutrient acquisition.…”
Section: Introductionmentioning
confidence: 83%
“…Additional research will be needed to characterize the particular molecular mechanisms at play, and the assay we describe can be interfaced with reverse genetic approaches to provide a genetic and mechanistic basis for the observed responses. To this end, we have developed a robust and reliable in vivo RNAi protocol to suppress genes of interest in the B. malayi L3 stage (Song et al ., 2010), whilst others have shown that RNAi can be applied to other life stages of the parasite in vitro (Aboobaker and Blaxter, 2003; Ford et al ., 2009; Landmann et al ., 2012; Singh et al ., 2012; Winter et al ., 2013; Luck et al ., 2016; Misra et al ., 2017; Verma et al ., 2017). This receptiveness to RNAi, combined now with assays to interrogate sensory phenotypes, advances B. malayi as a tractable system to better understand sensory biology in filarial worm parasites.…”
Section: Discussionmentioning
confidence: 99%